EFFECT OF COMPETENCY AND JOB PLACEMENT ON PERFORMANCE WITH JOB SATISFACTION AS INTERVENING VARIABLE (Study at the Regional Civil Service Agency of Bondowoso Regency) - Fendy Ernawan; Nurul Qomariah; Abadi Sanosra (Krisnadwipayana International Journal of Management Studies, 2021)
This research is motivated by several gaps or differences in research results with expert opinions, also supported by some research problem data, namely based on ASN mutation data showing that there are still many ASN whose work placements are not in accordance with their field competencies. Based on the results of the identification of employee performance analysis in 2020, it shows that the realization of ASN work in Bondowoso Regency has not been maximized. The purpose of this study was to determine directly or indirectly the effect of employee competence and job placement on employee performance through job satisfaction as an intervening variable for all structural employees of the Bondowoso Regency Government. The population of this study was 3,051 employees, while the number of samples was 354 using purposive sampling technique. The analysis technique used is the Structural Equation Model (SEM) using WarpPLS 5.0. The results of data analysis show that employee competence and job placement have a significant effect on job satisfaction, (2) employee competence and job placement and job satisfaction have a significant effect on employee performance, (2) employee competence and work placement have a significant effect on employee performance through job satisfaction as intervention variables.